Wine tokenisation: the opportunity of DLT technology for the economic and social challenges of the wine sector - Ibáñez-Jiménez, Javier W.; Palomo-Zurdo, Ricardo (REVESCO. Revista de Estudios Cooperativos, 2024)
Wine tokenisation is one of the most formidable challenges faced by wine industry in the process of digitalisation for the shortcoming years. The winegrowing and wine sector throughout the whole extension of its chain of value are experimenting a radical transformation. Relevant AI, DLT and IoT actors, and leaders in the scientific community in chemistry, engineering, economy and law share the idea of shifting vine and wine interprofessional cooperation in digital identity and data sharing in vine and wine digital authentication and market traceability processes. This contribution poses key issues thereto, within the context of the development of new DLT tokenised wine markets and social hubs, envisaging transdisciplinary ways to overcome main economic threats and legal barriers.